"As Organizações Sociais (OS) e as Organizações da Sociedade Civil de Interesse Público (OSCIP)" - Albuquerque, Pedro Sotero de (2008)
The reform process of the Brazilian State that has been taking place over the last few decades has brought about a revision process of the concepts pertaining to the rendering of public services and the fomentation of public interest activities, focused on the need to reduce State participation in economic and social spheres. Amongst measures adopted for such, judicial titles for Social Organizations and Civil Society Organizations of Public Interest will be bestowed on beneficiary entities under specific legal conditions. Nonetheless, like any innovation to constitutional administrative law, the advent of these contracting modalities have caused the surfacing of innumerous doctrinarian and jurisprudence discussions, which postulate for a revision of the concepts that were previously consecrated in our positive judicial order. This undertaking is focused on analyzing these judicial titles and their relation to administrative activities and civil prerogatives, from the Brazilian constitutional law point of view